Highlights of practical applications of cyber-physical multi-agent systems : international workshops of PAAMS 2017, Porto, Portugal, June 21-23, 2017, Proceedings /: international workshops of PAAMS 2017, Porto, Portugal, June 21-23, 2017, Proceedings. ([2017]) - Unknown
No abstract available